A Chinese Herbal Decoction, Modified Yi Guan Jian, Induces Apoptosis in Hepatic Stellate Cells through an ROS-Mediated Mitochondrial/Caspase Pathway. (26th August 2010) - Lin, Hung-Jen; Tseng, Ching-Ping; Lin, Chia-Fan; Liao, Mei-Huei; Chen, Chuan-Mu; Kao, Shung-Te; Cheng, Ju-Chien
Abstract : The Chinese herb modified Yi Guan Jian (mYGJ) is an effective regimen that is usually used in outpatients with chronic liver diseases such as fibrosis and cirrhosis. However, the mechanism for the action of mYGJ on liver fibrosis is not yet clear. In this study, we found that mYGJ induced hepatic stellate cells (HSCs) apoptosis concomitant with the downregulation of Bcl-2 expression and slight elevation of Bax level. Moreover, the reactive oxygen species (ROS) were generated in the early stages of mYGJ-induced HSCs apoptosis to facilitate calcium and cytochrome c release from the mitochondria to cytosol. Subsequently, caspase 9 and caspase 3 were activated. Furthermore, the activation of ER stress-associated caspase 12 in HSCs was also evaluated. Together, we report the first evidence-based study to demonstrate that mYGJ decoction induces HSCs apoptosis through ROS accumulation and the intrinsic apoptosis pathway. These findings provide rationale for further clinical investigation of traditional Chinese medicine recipes against liver fibrosis.